2011
DOI: 10.1007/s11064-011-0532-0
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosylphosphorylcholine Attenuated β–Amyloid Production by Reducing BACE1 Expression and Catalysis in PC12 Cells

Abstract: Abnormal accumulation of β-amyloid (Aβ) is the main characteristic of Alzheimer's disease (AD) brain and Aβ peptides are generated from proteolytic cleavages of amyloid precursor protein (APP) by β-site APP-converting enzyme 1 (BACE1) and presenilin 1 (PS1). Sphingosylphosphorylcholine (SPC), a choline-containing sphingolipid, showed suppressive effect on Aβ production in PC12 cells which stably express Swedish mutant of amyloid precursor protein (APPsw). SPC (> 3 μM) significantly lowered the accumulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In the present study, artemisinin significantly inhibited the activation of NF‐κB and NALP3 inflammasome, thus leading to the decreased production of downstream cytokines (TNFα, IL‐6, IL‐1β). In fact, the antiinflammatory effects of artemisinin from NF‐κB inhibition have been proven in models of lupus nephritis, experimental autoimmune encephalomyelitis, and other disease . Our study first demonstrated the antiinflammatory effects of artemisinin in AD animal model.…”
Section: Discussionmentioning
confidence: 53%
“…In the present study, artemisinin significantly inhibited the activation of NF‐κB and NALP3 inflammasome, thus leading to the decreased production of downstream cytokines (TNFα, IL‐6, IL‐1β). In fact, the antiinflammatory effects of artemisinin from NF‐κB inhibition have been proven in models of lupus nephritis, experimental autoimmune encephalomyelitis, and other disease . Our study first demonstrated the antiinflammatory effects of artemisinin in AD animal model.…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, other different compounds lower BACE1 activity through the inhibition of NF‐κB pathway, as described recently (52, 53), suggesting that this pathway could be a useful therapeutic target.…”
Section: Bace1 Structurementioning
confidence: 59%
“…However, a variety of correlative signals have been observed in AD patients and relevant cellular systems. For example, two enzymes partially responsible for LPA or S1P production, autotaxin or SPHK2, respectively, have been reported to be upregulated in AD brain samples [145,146], while S1P exposure reduces the activity of the β-site APP cleaving enzyme-1 (BACE1) that causes abnormal amyloid β (Aβ) accumulation, a characteristic feature of AD [145,147]. It has also been reported that S1P levels are reduced in AD patients [148] and that Aβ downregulates another S1P synthetic enzyme, SPHK1, while overexpression of SPHK1 reduces Aβ-induced death [149].…”
Section: Lpa and S1p Receptors As Promising Therapeutic Targets Inmentioning
confidence: 99%